Pengaruh Current Ratio (CR) Dan Debt To Equity (DER) Terhadap Pertumbuhan Laba Pada PT.Tri Banyan Tirta,Tbk. Periode 2013-2022 - Hasudungan, Gilbert; Faisal (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
The aim of this research was to determine the influence of the Current Ratio (CR) and Debt to Equity (DER) on Profit Growth at PT Tri Banyan Tirta Tbk. period 2013 – 2022. The research method used in this research is quantitative using statistical tests which include multiple linear regression tests and classical assumptions. In the classic SPSS assumptions used by researchers, namely normality, multicollinearity, autocorrelation and heteroscedasticity tests. Partially the author uses the t test, while simultaneously the author uses the F test which is then continued by using the coefficient of determination test. Based on the results of the t test research, it is stated that the Current Ratio (CR) has no effect on Profit Growth with a calculated t of 1.020 < t table 2.446 with a significant level of 0.052 And for Debt to Equity (DER) it partially has no effect on profit growth because the calculated t value is 1.115 < t table 2.446 with a significance level of 0.306. For the F test, the Fcount value was 0.707, while the Ftable was 4.74 with a significance level of 0.525. which means there is no simultaneous influence between Current Ratio (CR) and Debt to Equity (DER) on Net Profit at PT Tri Banyan Tirta Tbk. The resulting coefficient of determination was 16.8%, which means it only had an influence of 16.8%, while 83.2% was the influence of other factors not examined in the author's research.